I am a Muslim Song: Method of Improving Speaking Skills for Early Childhood - Erlangga, Rifqi Aulia; Abdul Syukur (Social Science Studies, 2024)
Research Aims: This study aims to analyze the effectiveness of learning Islamic education and English using the song I am a Muslim as a medium for early childhood (ages 4-12) through an experimental study. Design/methodology/approach: This research employs an experimental method involving 32 children from various regions in Indonesia. The song was played three times a day for one month, and the children's progress was observed through video recordings and interviews with close family members. The data were analyzed using a qualitative descriptive approach. Research Findings: The research findings indicate that 18 children experienced significant improvements in English proficiency and understanding of religious values, while the other 14 showed varying levels of progress. Factors such as age, learning methods, and family support influenced the success rate of the learning process. Theoretical Contribution/Originality: This study provides theoretical contributions to language and religious education by emphasizing the role of songs as an effective learning medium. It also highlights the importance of experiential learning approaches in enhancing language skills and understanding of religious values.